Pemetaan Potensi Desa dalam Rangka Pengembangan Unit Usaha BumDes Tamer Mandiri - Neneng Salmiah; Satria Tri Nanda; Intan Adino (SULUH: Jurnal Abdimas, 2020)
The community service program aims to provide knowledge to the village government and village community about the potential of Tanah Merah Village and assistance in mapping the potential of the village. With this service activity, it is expected that the knowledge of the village government and the village community about the potential of the village owned will increase so that the results of the village discussion will be decided upon which business units will be formed to develop the Tamer Mandiri BUMDes business unit. The method used in this activity is to conduct pre-test, counseling, simulation, question and answer, post test, and evaluation. The results of the community service activities are as expected, namely an increase in knowledge of village potential mapping and an understanding that each village must have the potential to be developed into the BUMDes Tamer Mandiri business unit.